MODERN DIAGNOSIS OF INFERTILITY ASSOCIATED WITH GENITAL TUBERCULOSIS - Клинышкова, Татьяна Владимировна; Яковлева, Анастасия Алексеевна (Mother and Baby in Kuzbass, 2018)
The aim of the research – definition of informativeness of indices of local humoral immunity to M. tuberculosis and laparoscopic data in patients with confirmed tubal-peritoneal infertility associated with genital tuberculosis.Materials and methods. Conducted a prospective study that included 32 patients from 23 to 39 years, which was performed laparoscopic treatment for infertility, divided into two groups depending on the presence or absence of genital tuberculosis at the time of research and history. Evaluated the state of the local specific humoral immunity at the level of specific immunoglobulins to M. tuberculosis in the peritoneal fluid.Results. In the evaluation of local immunity showed increased level of IgM to M. tuberculosis in the primary group (p = 0.006). The evaluation of the diagnostic value of increased IgM to M. tuberculosis in whole peritoneal fluid of the patients with tubal-peritoneal infertility. A diagnostic significance of complex endoscopic signs and indicators of local humoral immunity in patients with infertility associated with genital tuberculosis.Conclusion. When tubal-peritoneal infertility are grounded assessment informative for the timely detection of genital tuberculosis indicators: the level of peritoneal IgM to M. tuberculosis, peritoneal symptoms, level of occlusion of the fallopian tubes, the severity of adhesions with subsequent etiotropic therapy.
Keywords: genital tuberculosis; tubal factor infertility; peritoneal fluid; diagnostics